Pythium Species Associated with Damping-off of Pea in Certified Organic Fields in the Columbia Basin of Central Washington - Alcala, Avc (Alcala, Ana Vida C.); Paulitz, Tc (Paulitz, Timothy C.); Schroeder, Kl (Schroeder, Kurtis L.); Porter, Ld (Porter, Lyndon D.); Derie, Ml (Derie, Michael L.); Du Toit, Lj (Du Toit, Lindsey J.)
Organic vegetable production accounted for 19 percent of the total organic acreage in Washington State in 2013, with 1,700 ha of certified organic vegetable pea. However, production is challenged constantly with the threat of poor emergence after planting due to damping-off caused by Pythium spp. A survey of Pythium spp. in organic vegetable production areas of the semiarid Columbia Basin of central Washington was carried out in fall 2009 to identify species associated with damping-off during early spring planting. Of 305 isolates baited from soil sampled from 37 certified organic fields, 264 were identified to 16 Pythium spp. by sequencing the internal transcribed spacer region of ribosomal DNA. A soil DNA-CFU regression curve was developed using real-time quantitative polymerase chain reaction assays for each of the three predominant pathogenic species (Pythium abappressorium, the P. irregulare complex, and P. ultimum var. ultimum)found in soil sampled from the 37 fields The P. irregulare complex, P. abappressorium, and P. ultimum var. ultimum were detected in 57, 78, and 100 percent of the fields sampled, respectively. A regression analysis was used to determine that P. ultimum var. ultimum ranged from 14 to 332 CFU/g of soil in the 37 fields, the P. irregulare complex ranged from 25 to 228 CFU/g of soil, and P. abappressorium DNA was below the quantifiable limit. In summary, P. ultimum var. ultimum was the most prevalent pathogenic Pythium sp. detected in certified organic fields in the semiarid Columbia Basin of central Washington but multiple Pythium spp. may be associated with damping-off in cool and wet, early spring planting conditions.
Keywords: POLYMERASE-CHAIN-REACTION; ROOT-ROT; SOIL; WHEAT; SPP; DISEASE; SEED; IDENTIFICATION; PATHOGENICITY; TEMPERATURE